O poeta entre o literário, o político e a polêmica: a recepção de Dante, no Romantismo francês - Mello, Celina Maria Moreira de (Revista de Italianística, 2016)
This essay draws a panorama of reception, in France, of the work of the poet Dante Alighieri, by scholars, translators, painters, and poets, in their role of cultural mediators, in a socio-historical and discursive perspective. Two different appropriations of the work of the Florentine poet are demonstrated as an example: Dante seen as a dangerous socialist Templar and a controversy, in the press, provoked by Dante’s biography, by Charles-Claude Fauriel (1772-1844), published in the Revue des Deux Mondes on October 1st, 1834. In addition to the conflicting positions in a perspective that aimed to constitute the literary field autonomy, we can see the confrontation of rival groups and publishing vehicles, the same happens with the reading of a chapter of narratives focused on the construction of national identities.